2011
DOI: 10.1088/1468-6996/12/5/054101
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput technology for novel SO2oxidation catalysts

Abstract: We review the state of the art and explain the need for better SO 2 oxidation catalysts for the production of sulfuric acid. A high-throughput technology has been developed for the study of potential catalysts in the oxidation of SO 2 to SO 3 . High-throughput methods are reviewed and the problems encountered with their adaptation to the corrosive conditions of SO 2 oxidation are described. We show that while emissivity-corrected infrared thermography (ecIRT) can be used for primary screening, it is prone to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…6 Catalysts synthesized by flame spray pyrolysis have been investigated for their activity for hydrocarbon/NO xoxidation in 2009. 15 Recent ecIRT projects deal with hydrogenations 16,17 and hydrodesulfurization, SO 2 oxidation, 18 the oxidation of waste gases in the presence of methyl bromide 19 and the Deacon process. EcIRT has become part of the bachelor of chemistry education at the University of Saarland and is mediated in lectures and laboratory exercises.…”
Section: ■ Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Catalysts synthesized by flame spray pyrolysis have been investigated for their activity for hydrocarbon/NO xoxidation in 2009. 15 Recent ecIRT projects deal with hydrogenations 16,17 and hydrodesulfurization, SO 2 oxidation, 18 the oxidation of waste gases in the presence of methyl bromide 19 and the Deacon process. EcIRT has become part of the bachelor of chemistry education at the University of Saarland and is mediated in lectures and laboratory exercises.…”
Section: ■ Applicationsmentioning
confidence: 99%
“…XRF experiments confirmed that sulfatization of the materials, resulting in emissivity and temperature changes, were responsible for the temperature raise. 18 Reflections. Materials of high reflectivity, such as steel, can reflect IR radiation, which is detected by the camera.…”
Section: Misinterpretation Of Irt Datamentioning
confidence: 99%
“…An oxidation of other typical exhaust gas components like CO might give false positive results. Furthermore, side reactions between reaction components and sample material are known in literature, e.g., sulfur decomposition from mixed metal sulfides [60] or sulfatization of Cu with SO 2 [65]. Images can be taken in different atmospheres to test for this behaviour.…”
Section: Emission Corrected Infrared Thermography Resultsmentioning
confidence: 99%
“…The ecIRT method, its general applications, advantages and drawbacks were detailed in a recent review article . The technology developed as well as the applicability of the ecIRT method for investigation of SO 2 oxidation catalysis was already subject of another publication . Therefore most details of the technology applied here are given in ref .…”
Section: Resultsmentioning
confidence: 99%
“…Only for some niche applications other catalyst systems like noble metal based catalysts or iron based catalysts (for high temperature processes) , are used or at least discussed. [For a more general overview regarding the current research efforts in sulfuric acid catalysis and the mechanism of the catalyzed SO 2 oxidation see the introduction of our review article from 2011 …”
Section: Introductionmentioning
confidence: 99%